Corpus Optimization: Socialization and Training of English Teachers in Islamic Boarding Schools : Optimalisasi Korpus: Sosialisasi dan Pelatihan Guru Bahasa Inggris di Pondok Pesantren - Agustina, Yulia Agustina; Prasetianingrum, Ary; Riadi Jaelani, Selamet (Universitas Lancang Kuning, 2025)
The goal of the two-days